Uncovering "Community': Challenging an Elusive Concept in Development and Disaster Related Work - Titz, Alexandra; Cannon, Terry; Krüger, Fred (Societies, 2018)
In all areas of academic or practical work related to disaster risk, climate change and development more generally, community and its adjunct community-based have become the default terminology when referring to the local level or working with the people'. The terms are applied extensively to highlight what is believed to be a people-centred, participatory, or grassroot-level approach. Today, despite, or because of, its inherent ambiguity, community' tends to be used almost inflationarily. This paper aims to analyse the way the concept of community' has come into fashion, and to critically reflect on the problems that come with it. We are raising significant doubts about the usefulness of community' in development- and disaster-related work. Our approach is to first consider how community' has become popular in research and with humanitarian agencies and other organisations based on what can be considered a moral licence' that supposedly guarantees that the actions being taken are genuinely people-centred and ethically justified. We then explore several theoretical approaches to community', highlight the vast scope of different (and contested) views on what community' entails, and explain how community' is framing practical attempts to mitigate vulnerability and inequity. We demonstrate how these attempts are usually futile, and sometimes harmful, due to the blurriness of community' concepts and their inherent failure to address the root causes of vulnerability. From two antagonistic positions, we finally advocate more meaningful ways to acknowledge vulnerable people's views and needs appropriately.
Created from Fastlane, WoS look-up